Chaos Is a Gift? Leading Oneself in Uncertain and Complex Environments. - Zyl, Ebben van (Knowledge Resources, 2020)
Chaos | volatile | uncertain | complex | time | pandemic | coronavirus | leading | private sector | conflict | wisdom | change | Socrates | leadership | unpredictable | difficult | self-care | humanness | business | unpredictable | perspectives | stillness | VUCA | higher education | Zimbabwe | South Africa | Namibia | resilience | optimism | adaptability | university | psychology | environment | conflict | post-conflict | resolution | peace | build | grow | organisation | liminal | lessons | religious | outcomes | recommendation | conclusion | strategy | strategic.